Insights on the Sargassum horneri golden tides in the Yellow Sea inferred from morphological and molecular data. (18th April 2018) - Liu, Feng; Liu, Xingfeng; Wang, Yu; Jin, Zhe; Moejes, Fiona Wanjiku; Sun, Song
Abstract: Large‐scale drifting Sargassum biomass, known as golden tides, has caused considerable damage to the local environment and economy associated with the Yellow Sea of China. To understand the reoccurrence of Sargassum horneri golden tides in the Yellow Sea, large‐scale spatio‐temporal sampling was performed across nine cruises and five coastal surveys. Morphological data indicated that the floating S. horneri thalli with differing reproductive timing coexisted in the Yellow Sea. A total of 196 S. horneri samples had identical sequences of partial cox3 and rbc L‐S spacer region, revealing very low genetic diversity in the floating biomass. A total of 19 haplotypes for partial cox3 previously found in the Yellow Sea were not detected in our large‐scale sampling. Based on four novel mtDNA markers, the 196 samples could be further distinguished into two forms, which varied in proportions at various locations, but coexisted in each of the spatio‐temporal sampling. These results indicated that the floating Sargassum biomass in the Yellow Sea came from only two dominating haplotypes. The novel findings uncovered by this work will provide further insight into the underlying mechanisms of reoccurring golden tides in the Yellow Sea, and lead to the improved management of the Sargassum biomass.